Application of Smart Technology and Equipment in Horticulture (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
As an important aspect of modern agriculture, horticulture plays a crucial role in beautifying the environment and enriching human nutrition. Now, due to the application of intelligent devices in all aspects of agriculture, horticulture—an agricultural form that requires more refined management and operation—has begun to pursue intelligence and intensification. Therefore, the demand for advanced gardening technology and intelligent equipment is growing. In order to develop intelligent technology and equipment that can aid in gardening, beautify the environment, and support the cultivation and breeding of plants, research is needed to enhance the popularity of intelligent equipment and the survival rate of breeding. Successful breeding can enrich our choices, and automated gardening can accelerate urban greening. Similarly, the use of intelligent technology and equipment in intensive horticulture can not only reduce the cost of manpower, but also strengthen the accuracy and efficiency of management, thus increasing the output. This Special Issue focuses on the intelligent technology and equipment currently utilized to beautify the environment, promote agricultural intensification, and cultivate and breed species of plants.